Overview Of Clean And Healthy Living Behaviors In Coastal Communities In Sibolga City In 2020 - Della Winda Gultom; Herlina; Nurul Hikmah Simatupang (Science Midwifery, 2020)
Clean and healthy living behavior is an action that is carried out consciously so that a person and the community are independent in health and can play an active role in improving health in the community environment. This study aims to identify a picture of clean and healthy living behaviors in coastal communities in Sibolga City. The design of this study is descriptive quantitative. Sampling technique with non probability sampling technique with purposive sampling approach with a total sample of 92 people. This research was conducted from July to October 2020. Data collection was carried out by providing questionnaires about PHBS to willing respondents. The questionnaire consists of respondents' demographic data, knowledge questionnaires, attitude questionnaires, and action questionnaires. The results showed that the majority of coastal communities in Sibolga City had good knowledge, namely 90 respondents (97.8%), positive attitudes, namely 92 people (100%), and community actions were included in the good category, namely as many as 78 people (84.7%) about Clean and Healthy Living Behavior. From the results of the study, it is hoped that the community can increase knowledge, attitudes, and actions in behaving clean and healthy.